Compton radiation of an electron in the field of running plane linear polarized electromagnetic wave - Drebot, I.; Grigor'ev, Yu.; Zelinsky, A. (Вопросы атомной науки и техники, 2009)
Results of integration of Lorentz force equation for a relativistic electron, moving in the field of running, plane, linear polarized electromagnetic wave are presented in the paper. It is shown that electron velocities in the field of the wave are almost periodic functions of time. Expansion of the electromagnetic field in a wave zone into generalized Fourier series was used for calculations of angular spectrum of electron radiation intensity. Expressions for the radiation intensity spectrum are presented in the paper. The derived results are illustrated for electron and laser beam parameters of NSC KIPT X-ray generator NESTOR. Simultaneously, derived expressions give possibilities to investigate dependence of energy and angular Compton radiation spectrum on phase of interaction and the interacting wave intensity.